Berith as a Socio-Political and Economic Regulatory Mechanism in Ancient Israel and Traditional Ẹ̀gbá-Yorùbá Society (2014)
Berith, a concept similar to ìmùlẹ̀ among the Ẹ̀gbá-Yorùbá of South-Western Nigeria, is a pact ratified by oath, binding two or more parties in a relationship of moral commitment to certain stipulations. It was used to regulate socio-political and economic life in ancient Israel. Previous studies on Berith have focused on its legal aspect, neglecting its moral basis as a means of effectively regulating and controlling socio-political and economic aspects of human society in ancient Israel and its relevance to the traditional Ẹ̀gbá-Yorùbá sociocultural context with shared experiences. This study, therefore, examined the effectiveness of berith as a means of regulating socio-political and economic life in ancient Israel as replicated by ìmùlẹ̀ among traditional Ẹ̀gbá-Yorùbá. The work was premised on Manus’ intercultural hermeneutics which relates the Bible to African socio-cultural situations. The historical-critical method was used to analyse relevant texts (2 Kgs.22:8-23:3; Exod.20:22-23:33; Deut.6:1-28:69), taking the Leningrad Codex as the vorlage. One thousand copies of a questionnaire were purposively administered in traditional Ẹ̀gbá -Yorùbá homesteads in five local government areas across Ogun and Oyo states, Nigeria. Forty key informants including The Aláké of Ẹ̀gbáland, The Olórí-Pàràkòyí of Ìjejà, a magistrate, 22 Ẹ̀gbá Chiefs, and 15 clergymen were interviewed. A focus group discussion (FGD) was held with the Aláké Regency Council in session. Observation was conducted at the traditional courts at Aké Palace and Olúwo’s residence. Data generated were subjected to exegetical analysis and percentages. Three stipulations of berith were applied in ancient Israel: the lex talionis (Exod.21:22-25), the law of restrictive royalty (Deut.17:14-15) and the law of standard metering (Deut.25:13-16). In Ẹ̀gbá land, The Ògbóni enforced retributive justice and restricted royalty to a family while the Pàràkὸyí enforced market standards through ìmùlẹ̀. Berith produced bonding experiences by creating artificial kinship ties, replicated in ìmùlẹ̀ as Alájọbí, and annual religious convocations (Deut.16:16), not exactly replicated in Ẹ̀gbáland where Ògbóni, Pàràkὸyí and Olórógun held religio-political meetings tri-weekly. Berith bound the hitherto autonomous Israelite tribes in religious commonwealth through common allegiance to YHWH (Deut.12:5-7). In ìmùlẹ̀, the earth stood as the common source-matter, binding 300 traditional Ẹ̀gbá-Yorùbá clans under one central Ògbóni. Berith like ìmùlẹ̀, imposed socio-religious obligations requiring members of the commonwealth to seek each other’s personal wellbeing (Deut.15:39-43), material security (Exo.23:4) and financial stability (Deut.15:7-11). About 90% of the respondents affirmed that ìmùlẹ̀ effectively regulated political and socio-economic behaviour of traditional Ẹ̀gbá by fear-appeal through potent oath-taking. All the key informants agreed that perceived grievous consequences associated with breaking ìmùlẹ̀ coupled with anticipated rewards for upholding it motivated the people towards honesty in their social, political and economic activities. The FGD revealed that ìmùlẹ̀ was effective because it employed potent oath implements. Berith in ancient Israel is approximately equivalent to ìmùlẹ̀ in Ẹ̀gbáland based on the shared conceptual experiences of the two societies. Thus, the effectiveness of the concept in regulating and controlling socio-political and economic activities in each case was anchored to these shared experiences